Pengaruh Risiko Operasional, Risiko Kredit, dan Risiko Likuiditas terhadap Kinerja Perusahaan - Eduard Ary Binsar Naibaho; Fikram Ali Rachman (Jurnal Kajian Akuntansi, 2025)
This study aims to test and obtain empirical evidence regarding the impact of operational risk, credit risk, and liquidity risk on firm performance. The independent variables used in this study include operational risk, credit risk, and liquidity risk. Firm performance is measured using return on assets (ROA) and Tobin’s Q as dependent variables. The sample used consists of secondary data from the financial statements of non-financial sector companies published on the official website of the Indonesia Stock Exchange during the period 2018-2023, with a total of 606 data points. The sampling technique applied is purposive sampling, and the data analysis is conducted using multiple linear regression with the help of STATA software. The results of the study indicate that operational risk does not affect company performance (ROA) and has a negative effect on company performance (Tobin’s Q), credit risk positively affects firm performance, and liquidity risk negatively affects firm performance.